The hydraulic architecture of an arborescent monocot: ontogeny‐related adjustments in vessel size and leaf area compensate for increased resistance. Issue 1 (26th March 2021) - Yang, Dongmei; Zhang, Yinshuang; Zhou, Dan; Zhang, Yong‐Jiang; Peng, Guoquan; Tyree, Melvin T.
Summary: Bamboos are arborescent monocotyledons that have no secondary growth, but can continually produce conduits with diameters appropriate to the current size of the plant. Here, we studied bamboo hydraulic architecture to address the mechanisms involved in compensating for the increase in hydraulic resistance during ontogeny. We measured the hydraulic weighted vessel diameters ( D h ) at different distances from the apex along the stem of Bambusa textilis . The hydraulic resistance of different components and individuals of different heights were quantified using the high‐pressure flowmeter method. The D h showed tip‐to‐base widening with a scaling exponent in the range of those reported for trees. Although theoretical hydraulic conductivity decreased from base‐to‐tip, leaf‐specific conductivity did not change. Leaves contributed the most to the whole‐shoot hydraulic resistance, followed by the leaf‐bearing branches. Roots contributed c . 13% to whole‐plant resistance. Interestingly, taller individuals showed lower whole‐shoot resistance owing to an increased number of resistances in parallel (side‐branches), while leaf‐specific resistance was independent of plant size. Tip‐to‐base vessel widening and height‐independent constant leaf‐specific conductance could be mechanisms for hydraulic optimization in B. textilis . Similar patterns have also been found in woody plants with secondary growth, but this bamboo exhibits them without secondary growth.